Living Architecture: Toward Energy Generating Buildings Powered by Microbial Fuel Cells - You, Jiseon; Rimbu, Gimi A.; Wallis, Lauren; Greenman, John; Ieropoulos, Ioannis (Frontiers in Energy Research, 2019)
In this study, possibilities of integrating the microbial fuel cell technology and buildings were investigated. Three kinds of conventional house bricks from two different locations were tested as MFC reactors and their electrochemical characteristics were analysed. European standard off-the-shelf house bricks generated maximum power of 1.2 mW (13.5 mW m-2) when they were fed with human urine. Ugandan house air bricks produced a maximum power of 2.7 mW (33.3 mW m-2), again with human urine. Different cathode types made by surface modification using two kinds of carbon compound and two PTFE based binders were tested in both wet and dry cathode conditions. The effects of both anode and cathode sizes, electrode connection, electrode configuration and feedstock on brick MFC power generation were also studied. Water absorption test results showed higher porosity for the Ugandan air bricks than European engineering bricks, which contributed to its higher performance. This study suggests that the idea of converting existing/future buildings to micro-power stations as well as micro-treatment plants with the help of MFC and other renewable technologies integrated together is achievable, which will be a step closer to truly sustainable life.